Allelopathic Effect of Root Exudates of Two Sunflower Cultivars on Companion Weeds - A. Tawfiq, Arwa; S. Alsaadawi, Ibrahim (Iraqi Journal of Science, 2026)
The effects of root exudates of two sunflower cultivars (Shumoose and SinAltheeb) were studied on companion weeds during the growing season of 2012.Results showed the ability of both cultivars to affect weed population and growthwith the superiority of cultivar Shumoose in suppression of weed density at 60 and120 days after sowing compared to Sin Altheeb. Weed biomass was significantlyreduced up to 90 and 71% by Shumoose and Sin Altheeb cultivars, respectively.Stair case experiment indicated that root exudates of Shumoose cultivar showedmore suppression to weeds than Sin Altheeb giving additional evidence for thesuperiority of Shumoose cultivar in its allelopathic weed suppression. Chemicalanalysis by High performance liquid chromatography indicate the presence of ninecompounds in root exudates of Sin Altheeb and eight compounds in Shumoose, andall are Phenolic in nature with differential concentrations between these cultivars Most of the isolated chemicals known for their inhibiting ability for germination andgrowth of plants, including weeds. Total of the isolated phenolics was doubled inShumoose than in Sin Altheeb.